“Implementación de reflectores con paneles fotovoltaicos para la iluminación de la cancha sintética del bloque B en la Universidad Técnica de Cotopaxi”. - Ayala Tipan, Wilson Alexis (2021)
The present research work of the Electromechanical Engineering major aims to implement reflectors with photovoltaic panels to illuminate the synthetic field of block B at Universidad Técnica de Cotopaxi, extension La Maná; To achieve this, the necessary measurements and calculations have been carried out to identify the most appropriate photovoltaic panel and illuminate the synthetic pitch, emphasizing the use and application of existing photovoltaic energy in Ecuador. In the development of this project, a photovoltaic lighting system with solar panels has been implemented, the same ones that have the function of charging their storage batteries to later supply energy to the reflectors. In addition, it was possible to comply with lighting standards and mathematical calculations to illuminate the area of the synthetic court, whose Surface is 1161.94 square meters; a total luminous flux of 108 060.42 lumens is required. However, six 18000 lumen reflectors were installed; whose power is 300 watts, distributed three on each side of the field to be illuminated; at an optimal angle of 4.35 degrees depending on its latitude; finally, we obtain a saving of 270 kWh per month and 3240 kWh per year, which represent economic expense of $338.25 dollars year; in this way, recovering the total investment in 3 years 8 months and 19 days with the implementation of this system.